Desenvolvimento de um sistema para aplicação dos conceitos da tecnologia cad3d-bim na indústria moveleira - Santos Junior, Walkyso dos (2012)
In this work was developed an information system to apply the concepts of CAD3D-BIM technology for the design activities of the furniture industry. The development of this system was based in an architecture comprised of two modules: a web interface to management the metadata of models from furniture's library and the combination of three-dimensional CAD software with a specific plugin to access the information from this model. To develop this system was also used a Data Base Management System (DBMS) designed to storage the information from models in a hierarchical way, based on concepts of Group Technology (GT). The centralization of information in a single database allows the automatic availability of any changes to all participants involved in a particular project when it‟s happens. Each module from system has its own connection to this database. Finally was developed a prototype from a 3D virtual environment to help create Virtual Reality projects in the web. A study from available technologies to create 3D web applications for execution in websites was done to support this development. The interconnection between modules and the database developed allowed the assembly of a system architecture to support the construction and exhibition of projects of the furniture industry in accordance with the concepts proposed by BIM (Building Information Modeling), using as object of study the furniture industry of state of Rio Grande do Norte